Diagnostic Accuracy of Prolactin Levels in Pituitary Microadenoma Keeping MRI as A Gold Standard - Bibi, Ayesha; Shoukat, Shaista; Shahbaz, Sumera; Bibi, Zakia; Samad, Abdul; Magsi, Farah (Biological and Clinical Sciences Research Journal, 2025)
Pituitary microadenomas are small, benign pituitary gland tumors often associated with elevated serum prolactin levels. Early detection is crucial for prompt management, but imaging with MRI remains the gold standard. Evaluating the diagnostic utility of serum prolactin levels can help streamline the diagnostic pathway, especially in resource-limited settings. Objective: The present study aims to assess the diagnostic accuracy of prolactin levels in diagnosing pituitary microadenomas, keeping MRI as the Gold Standard. Methods: After the ethical approval from the institutional review board, this cross-sectional study was conducted at the Department of Radiology, Jinnah Postgraduate Medical Centre, Karachi, from 03/December/2024 to 03/February/2025. Through non-probability consecutive sampling, 98 patients, aged 18–65 years, of either gender, with clinical suspicion of pituitary microadenomas and having serum prolactin levels ≥25 ng/mL, were included in the present study. Results: The sensitivity of serum prolactin in detecting pituitary microadenomas was 89.06%, indicating its ability to identify affected individuals correctly. However, the specificity was lower at 41.18%, suggesting a higher likelihood of false positives. The ROC curve analysis with an AUC of 0.866 for Prolactin level in predicting microadenomas, taking MRI as the gold standard. Conclusion: First-line diagnostic screening employing serum prolactin testing shows promising results in detecting pituitary microadenomas because of high sensitivity, yet requires an additional MRI examination to confirm the conclusive diagnosis of the condition.